Improving customer billing telephony using User Experience (UX) approach - Bidin, Raziera (2018)
User Experience (UX) is technology that fulfils an instrumental needs which include a subjective, situated, complex and dynamic encounter. UX represent the holistic view with of the pragmatic aspect and hedonic aspect. Nowadays, UX is become important issue and has been discussed by many researchers in developing web based system. While, telecommunications industry has gone through series of development efforts to make services always available to their consumers and to provide a good quality. Generally, telecommunication industry provide two main services such as telephony and internet with involved customer registration, billing and payment. However, the challenge confronting telecommunications industry is to meet the customer satisfaction in billing system such as the accurately, easy to understand, performance and resolving billing issue. Hence, the improvement of these issues can enhance the customer satisfaction. In this research, we are focusing on the accurate billing, easy to understanding and resolving billing issue. Therefore, we propose the web design of customer billing telephony system using UX approach that consider on the customer’s value experience. In order to well understand the concept, a thorough study on existing billing system is required by distributing the questionnaire to the respondent. Towards the end, the prototype will be developed and evaluation will be done by the respondent to prove the efficiency and correctness in billing process. It is expected that by implementing this approach, it will improve the customer billing telephony system and give the positive perceptions and experiences of a service lead to high customer satisfaction.